Towards a semantic segment of a research e-infrastructure: necessary information objects, tools and services. (1st January 2013) - Parinov, Sergey
Basically, semantic linkage technique is used to specify in computer-readable form relationships that definitely exist between information objects such as people, organisations and research outputs. Recently, developers also started using it to visualise scientists' opinions or scientific hypotheses (e.g. inference/deduction, impact/usage, theoretical hierarchy, etc.) about relationships between research objects. Based on CERIF link entity and the semantic layer, we propose a research e-infrastructure semantic segment, which allows scientists semantically link any pair of research objects within content of Research Information Systems (RIS). We discuss: (a) templates of a semantic linkage and a semantic meaning with focus on a semantic interoperability; (b) necessary tools and services for proper working of proposed segment of the research e-infrastructure. Assuming that scientists typically re-use research objects by making relationships between them, the proposed application gives the community a new ability and opens a new dimension for scientific creativity and opportunity for new scientometric studies.